Monetary regimes, the term structure and business cycles in Ireland, 1972–2018. (14th June 2020) - Stuart, Rebecca
Abstract: The literature emphasizes the role of monetary policy for the term structure's ability to predict business cycles. Between 1972 and 2018, Ireland experienced three monetary regimes: first, the Irish Pound was fixed to Sterling (1972–1979); second the Pound floated in a band when Ireland was a member of EMS (1979–1998); and third, as a member of the euro area (1999–2018). Using dynamic probit models and monthly data, I show that the term spread only had predictive power during the second regime, the only one in which the Central Bank of Ireland had discretion to set interest rates based on the domestic conditions.